2006
DOI: 10.1002/ange.200504266
|View full text |Cite
|
Sign up to set email alerts
|

Strukturmodell des membrangebundenen C‐Terminus des humanen lipidmodifizierten N‐Ras‐Proteins

Abstract: Etwa 5 bis 10 % aller zellulären Proteine weisen eine posttranslational erworbene Lipidmodifikation auf.[1] Insbesondere Proteine, die an der Signaltransduktion beteiligt sind, werden durch diese hydrophoben Gruppen an der Zellmembran verankert.[

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
2
0
0
1
Order By: Relevance
“…As the C terminus of the Ras protein is unstructured, the described mobile peptide conformation appears to be relevant for the structure of the full-length membrane-bound Ras protein. [125,127] A similar result was recently found for the binding of the completly lipidated N-Ras protein to model membranes. [127] The experimental results obtained for the Ras peptide were in excellent agreement with recent molecular-dynamics studies.…”
Section: Insertion Into Model Membranessupporting
confidence: 65%
See 1 more Smart Citation
“…As the C terminus of the Ras protein is unstructured, the described mobile peptide conformation appears to be relevant for the structure of the full-length membrane-bound Ras protein. [125,127] A similar result was recently found for the binding of the completly lipidated N-Ras protein to model membranes. [127] The experimental results obtained for the Ras peptide were in excellent agreement with recent molecular-dynamics studies.…”
Section: Insertion Into Model Membranessupporting
confidence: 65%
“…[125,127] A similar result was recently found for the binding of the completly lipidated N-Ras protein to model membranes. [127] The experimental results obtained for the Ras peptide were in excellent agreement with recent molecular-dynamics studies. [128] The molecular-dynamics simulations for a 10-ns time scale showed that the lipid chains of the peptide are more moble than those of the surrounding phospholipids chains.…”
Section: Insertion Into Model Membranessupporting
confidence: 65%
“…Ein ähnliches Ergebnis wurde für die Bindung des vollständigen lipidierten N‐Ras‐Proteins an Modellmembranen gefunden 127. Die für das Ras‐Peptid erhaltenen experimentellen Befunde stimmen ausgezeichnet mit neueren Moleküldynamikstudien überein 128.…”
Section: Biophysikalische Studien Mit Lipidierten Peptidenunclassified